A clinical picture and treatment optimization of acute forms of tick-born encephalitis - M. V. Nadezhdina; M. G. Toporkova; N. M. Gurary; N. A. Makhneva (Бюллетень сибирской медицины, 2008)
A comparative clinical and serological analysis of two groups compatible by sex, age and clinical forms of acute tick-born encephalitis was conducted among 68 patients with confirmed immune enzyme method. All patients received a single injection of high titrating Russian human tick-borne encephalitis immunoglobulin by the doze varying on the patient’s weight and particular decease. All patients received symptomatic therapy as well. There were 33 patients in the group II who have been taking anaferon during two weeks since the acute period. The patients of the groups I and II didn’t have any robust alteration of the feverish period duration and cerebrospinal fluid sanitation but it was discovered that the patients of the group II with focal form had reveal predominance of IgM titer on the second week of the disease development comparing with the same indicators among the patients of the group I with focal form. The findings show the possibility to recommend anaferon for complex treatment of the patients with tick-born encephalitis in acute period.